Вплив нагрівання на пускові властивості синхронного двигуна - Півняк, Геннадій Григорович; Кириченко, Віталій Іванович; Кириченко, Владислав Віталійович; Боровик, Роман Олексійович; Барабан, Віктор Вікторович; Бакутін, Андрій Вадимович (НТУ "ХПІ", 2010)
The influence of winding and discharge resistance heating on starting characteristics of 4000 kW synchronous motor is researched. The fact that their temperature instability is obligatory for guaranteeing the declared passport information in the process of synchronous motor designing is proved. The use of program controlled exciter that provides passport ratios of starting and synchronization torques and the number of succession starts without installed drive power margin is offered.
Influence of heating on starting properties of synchronous motor
Keywords: обмотка статора; опір активний; опір розрядний; енергія теплова; навантаження